Correlation of Lipid Profile & Acute Inflammatory Markers in Rheumatoid Arthritis (Academia Journal of Medicine, 2020)
Background: Rheumatoid arthritis (RA) primarily affect the synovium and is a chronic inflammation disease, which leads to joint damage and  bone destruction. Causes of significant morbidity are due to result of synovial inflammation, joint destruction and associated disability. Many  pieces of evidence suggest that proatherogenic disease associated with increased cardiovascular (CV) mortality is rheumatoid arthritis (RA).  Addition to genetic and conventional CV risk factors, chronic inflammation has emerged as a key component of this process. Cardiovascular  concerned demises shown a preferment in CRP among RA cases who have ongoing active inflammation that's why CRP can be self-sufficient  pointer for cardiovascular disease. Subjects and Methods: Current study has been conducted in Teerthanker Mahaveer hospital, Teerthanker  Mahaveer medical college. Data has been collected in duration of 12 months. After obtaining consent, data has been collected from 60  consecutive established case of rheumatoid arthritis. Almost equal number of participants were belonging to 30-39 years (16, 26.7%), 40-49  years (15, 25.0%), and 50-59 years (16, 26.7%) age groups. Very few participants were belonging to 20-29 years (4, 6.7%) and 60-69 years (9,  15.0%). Range of age was from 25 years to 69 years. Results: Pearson correlation coefficient of CPR with Total cholesterol, HDL-C,  Triglyceride, LDL-C and VLDL-C were -0.326, -0.269, -0.307, -0.310 and -0.307 respectively. All the correlation coefficients were  statistically significant (
Keywords: LDL; HTL; ESR; CRP; RA